Analyzing Poverty In Northern States Of Malaysia: An Asset Index Approach - Azhar, Nur Azirah Zahida Mohamad (2019)
Currently, Malaysia is using the Poverty Line Income (PLI) to measure poverty. Within this metric, income is the sole factor for measuring poverty because it is the easiest way to collect data. However, in its simplicity, it fails to capture the broader meaning and implications of poverty. The multidimensional poverty index (MPI) was introduced in Malaysia albeit in its preliminary stage of application to replace the income-based poverty measurement, and asset index which have established by researchers but not used in measuring poverty in Malaysia. A household might be poor in income, but assets may prevent them from being trapped in poverty, while non-poor in income household might have the possibility to be poor if they have less or no assets. With this problem statement, this study achieves three objectives. The first objective is to calculate the poverty of 302 households in the Northern States of Malaysia using the asset index and analyze the current state of poverty incidence with change under asset index, while second objective is to measure the change in asset index under the presence of shocks faced by the households. The results show that there are more households in the Northern States of Malaysia are being interpreted as being ‘poorer’ when poverty is measured using assets and with the presence of shocks as opposed to income alone. Besides that, poverty incidence of Malay households, households living in urban area and households with middle-aged heads have high poverty incidence, while households with a head of households that is single and highly educated have low poverty incidence.